Hydropolitics of China towards Transboundary Ile and Ertis River Basins (International relations and international law Journal, 2024)
Sharing water resources between countries is a huge political issue. There have been few instances in recent history in which such disagreements have led to violence or hostilities. China's hydropolitics regarding transboundary Ile (Ili) and Ertis (Irtysh) Rivers in Central Asia, as well as Brahmaputra and Mekong in South and Southeast Asia, in which China is an upstream country, clearly demonstrates how international water law underestimates the role of power in relations between countries in the same river basin (Zeitoun and Warner, 2005). The vast majority of the transboundary rivers, including Ile and Ertis, originate in Tibet and other mountainous regions of China adjacent to Southeast Asia. Reaching a satisfactory agreement on water allocation and quality control remains a major challenge for nation states. Particularly, Ertis and Ile rivers are the largest and most significant. The trend for our neighbor is to withdraw water from these basins for a purpose of developing the oil and gas fields, as well as cotton production in Xinjiang region.In recent years, sharp reduction in flow along the Ile River has been observed during vegetation season, which is fraught with big problems, primarily to environment and hydropower of Kazakhstan. In fact, China is one of three countries in the world that voted against the UN Convention on the Non-Navigational Use of International Watercourses. As a result, China’s plans for a grandiose construction of mega-dams as well as a water diversion projects from the transboundary rivers, are becoming a source of tension between riparian states, creating the preconditions for conflict potential between the neighboring countries of the Mekong, India, including Kazakhstan. In this regard, the article analyzes China's approach towards transboundary water management through the lens of “hydro-hegemony theory” for a more detailed understanding of its hydropolitics. Key words: transboundary rivers, Ili River, Irtysh River, water security, water politics, hydrohegemony.